2019
DOI: 10.1186/s13000-019-0892-3
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar myeloid sarcoma as the presenting symptom of acute myeloid leukemia: a case report and literature review of Chinese patients, 1999–2018

Abstract: BackgroundMyeloid sarcoma (MS), which represents a rare malignancy that comprises of myeloid blasts occurring at extra-medullary sites, closely correlates with the onset and relapse of acute myeloid leukemia (AML) and other hemopoietic neoplasm. Female genital system is an uncommon location of MS, with the vulvar MS being even rarer that only eight cases have been reported in English-written literature.Case presentationA 47-year-old woman presented with chronic ulceration on her vulva for one and a half month.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The female reproductive system is less involved, and it was reported that the cervix was the most involved organ, estimated at 40.0% (22/54) in Chinese patients, followed by the ovaries (23.6%,13/55). [ 5 ] In our case, the patient was diagnosed with cervical GS with mild abnormalities in her bone marrow test, which was not sufficient to diagnose AML. However, the patient relapsed rapidly and progressed to GS with AML during the follow-up.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The female reproductive system is less involved, and it was reported that the cervix was the most involved organ, estimated at 40.0% (22/54) in Chinese patients, followed by the ovaries (23.6%,13/55). [ 5 ] In our case, the patient was diagnosed with cervical GS with mild abnormalities in her bone marrow test, which was not sufficient to diagnose AML. However, the patient relapsed rapidly and progressed to GS with AML during the follow-up.…”
Section: Discussionmentioning
confidence: 80%
“…[ 6 , 11 13 ] Chemotherapy plus surgery (34.5%) was reported to be the most common option in Chinese patients with gynecological GS. [ 5 ] In our case, the patient underwent hysterectomy, bilateral adnexectomy, and AML-type chemotherapy. Regrettably, she relapsed 3 months after surgery and chemotherapy and developed to AML.…”
Section: Discussionmentioning
confidence: 99%
“…21 In another study, a case of a 47-year-old woman with MS of the vulva was reported who presented with symptoms of AML. 22 Also, Wang et al described a case of MS of the small bowel, kidney, and mesenteric lymph nodes in a 26-year-old male patient who suffered from intermittent upper abdominal pain. 23 In spite of a multitude of case-report studies, still little is known about the epidemiologic features of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five cases have been reported as case reports . Two relevant series comprising 19 cases were published (34)(35). The patient ages in the case reports ranged from 3 months to 58 years.…”
Section: Discussionmentioning
confidence: 99%